Antiretroviral therapy induces a rapid increase in bone resorption that is positively associated with the magnitude of immune reconstitution in HIV infection. (28th January 2016) - Ofotokun, Ighovwerha; Titanji, Kehmia; Vunnava, Aswani; Roser-Page, Susanne; Vikulina, Tatyana; Villinger, Francois; Rogers, Kenneth; Sheth, Anandi N.; Lahiri, Cecile Delille; Lennox, Jeffrey L.; Weitzmann, M. Neale
Abstract : Objective: Antiretroviral therapy (ART) paradoxically intensifies bone loss in the setting of HIV infection. Although the extent of bone loss varies, it occurs with virtually all ART types, suggesting a common pathway that may be aligned with HIV disease reversal. Using an animal model of immunodeficiency we recently demonstrated that immune activation associated with CD4 + T-cell reconstitution induces increased production of the osteoclastogenic cytokines RANKL and TNFα by immune cells, driving enhanced bone resorption and loss in bone mineral density. Design: To confirm these findings in humans, we investigated the early kinetics of CD4 + T-cell recovery in relation to biomarkers of bone turnover and osteoclastogenic regulators in a prospective 24-week cohort study. Methods: Clinical data and blood sampling for HIV-RNA PCR, CD4 + T-cell counts, bone turnover biomarkers, and osteoclastogenic regulators were obtained from ART-naïve HIV-infected study participants initiating standard doses of lopinavir/ritonavir plus tenofovir disoproxil fumarate/emtricitabine at baseline and at weeks 2, 8, 12, and 24 post ART. Results: C-terminal telopeptide of collagen (CTx) a sensitive biomarker of bone resorption rose by 200% above baseline at week 12, remaining elevated through week 24 (α<0.01), and was associated with significant increases in plasma levels of osteoclastogenic regulators [receptor activator of NF-kB ligand (RANKL), tumor necrosis factor alpha, (TNFα)]. Importantly, the magnitude of CD4 + T-cell recovery correlated significantly with CTx ( r s  = 0.387, α=0.01). Conclusion: Our data suggest that ART-induced bone loss occurs early, is aligned with early events of immune reconstitution, and these immune changes provide a unifying mechanism to explain in part the skeletal decline common to all ART. Abstract : Supplemental Digital Content is available in the text